A Strategy for Renormalizing Fiscal and Monetary Policies in Advanced Economies - Cottarelli, Carlo (IMF Staff Position Notes; Staff Position Note ;, 2009)
In response to the worst economic crisis since the 1930s, government budgets and central banks have provided substantial support for aggregate demand and for the financial sector. In the process, fiscal balances have deteriorated, government liabilities and central bank balance sheets have been expanded, and risks of future losses for the public sector have increased.